ANALYSIS OF THE SOCIAL FUNCTION OF LAND RIGHTS FOR PUBLIC INTEREST - Safitri, Adelia; Sugiharto, Dr. (jfpublisher, 2024)
This research examines the evolution of land rights in Indonesia, focusing on their social function. Drawing on von Savigny's perspective, which emphasizes the influence of family, nation, and state on law and culture, this research explores how these factors have shaped Indonesian land rights, blending customary and European legal traditions. This research aims to analyze the shift in land rights following the enactment of the Basic Agrarian Law (UUPA) in 1960, which transformed land control from communal and religious systems to state regulation for the benefit of the people. The UUPA establishes that all land rights carry a social function, requiring their use to align with public interest and community welfare. Using a normative juridical approach, this research reviews key legal frameworks, including Law No. 5 of 1960 and Law No. 2 of 2012. The research findings reveal that the state plays a central role in ensuring the social function of land, particularly through policies that balance individual rights with public benefit, aligning with utilitarian ideals. This research concludes that while land rights are guaranteed under Indonesian agrarian law, their social function is prioritized, ensuring land use serves public interest and promotes equitable development.